2017
DOI: 10.12740/pp/68848
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization feelings and depression symptoms in psoriasis patients

Abstract: It is still necessary to change the public attitude to patients with psoriasis. It is also very important to provide the patients with psychotherapeutic support aimed at enhancing their self-acceptance in order to overcome any feelings of stigmatization and to prevent them from depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 0 publications
6
38
0
3
Order By: Relevance
“…The results of previous studies analyzing the relationship between sex and stigmatization level in psoriasis are inconclusive. Some authors found higher stigmatization levels among women [27][28][29], whereas others did not observe significant sex-related differences in this parameter [16]. Similar to our study, Hrehoró w et al [30] did not find a statistically significant difference in the stigmatization levels of Polish females and males with psoriasis.…”
Section: Discussionsupporting
confidence: 85%
“…The results of previous studies analyzing the relationship between sex and stigmatization level in psoriasis are inconclusive. Some authors found higher stigmatization levels among women [27][28][29], whereas others did not observe significant sex-related differences in this parameter [16]. Similar to our study, Hrehoró w et al [30] did not find a statistically significant difference in the stigmatization levels of Polish females and males with psoriasis.…”
Section: Discussionsupporting
confidence: 85%
“…Internalization of the illness-related stigma may produce a feeling of guilt, and often the fear of being assessed by others may jeopardize one's emotional status and even lead to mental illness [13][14][15]. Persons with psoriasis are vulnerable to comments and remarks about their disease, which not infrequently results in social withdrawal, and may develop depression or even undertake suicide attempts [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a better understanding of the complex nature of the discussed dermatosis is extremely important in terms of diagnostics and therapy. It also helps to understand the feeling of anxiety, fear and distress among patients [9]. Mallbris et al indicate that the occurrence of psoriasis at an early age is associated with an increased risk of death attributed to cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Zespołem metabolicznym określa się współistnienie kilku zaburzeń, takich jak: otyłość brzuszna (obwód talii u kobiety ≥ 88 cm, u mężczyzny ≥ 102 cm), wzrost stężenia trójglicerydów ≥ 150 mg/dl, lipoprotein wysokiej gęstości (high-density lipoprotein -HDL; u kobiet ≤ 50 mg/dl, u mężczyzn ≤ 40 mg/dl), wartość ciśnienia tętniczego ≥ 130/85 mm Hg oraz stężenie glukozy we krwi na czczo ≥ 100 mg/dl [8]. U pacjentów z łuszczycą obserwuje się zaniżone poczucie własnej wartości, depresję, nadużywanie alkoholu, co w połączeniu z niewielką aktywnością fizyczną skutkuje wzrostem masy ciała [9]. Poza tym zaobserwowano, że pacjenci z łuszczycą relatywnie często nie index (BMI) and excess weight or obesity, which are independent risk factors for the development of cardiovascular diseases [11].…”
Section: W S T ę Punclassified
See 1 more Smart Citation